Carbon Interlayer Between CVD SiC and SiO2 in High‐Temperature Passive Oxidation. Issue 5 (9th February 2014) - Katsui, Hirokazu; Oguma, Miyuki; Goto, Takashi; Jacobson, N.
<x xml:space="preserve">Abstract</x> The oxidation behavior of high‐purity silicon carbide (SiC) prepared by chemical vapor deposition was investigated by thermogravimetry, transmission electron microscopy, and Raman spectroscopy in the temperature range 1534–1902 K in pure O2. The carbon layer formed at the SiC/SiO2 interface upon oxidation above 1784 K. Raman peaks corresponding to D‐ and G‐bands could be identified from the carbon layer. Bubbles were observed in the SiO2 scale after the oxidation at 1873 K. This could be attributed to the accumulation of CO gas at the SiC/SiO2 interface, resulting in the formation of the carbon layer and bubbles. These suggest that the oxidation rate of SiC is limited by the outward diffusion of CO in the SiO2 scale in this temperature range.